Drugs for children - a turning point in European law - Januszewicz, Paweł (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">New EU proposals on medicines for children, becoming effective end of 2006 are presented in this paper. This will create a new situation for pediatric patients, doctors and pharmaceutical industry, since nearly 50% of medicines registered in Europe are currently used “off-label” when prescribed for children aged 0–18.